Peran Pendidikan Luar Sekolah Dalam Penguatan Pendidikan Karakter - Susan Daniel; Yossita Wisman (FKIP Universitas Palangka Raya, 2022)
This manuscript is prepared to examine the values of life in the context of character building and education, as well as various factors that influence the dynamics of the application of life values. This paper is a study that analyzes several events as evidence of complex issues surrounding the character of the nation's children. The study discusses the understanding of education outside of school as strengthening character education. This is inseparable from the concern for the character of the nation's next generation. National character education is the development and inheritance of values derived from the outlook on life or ideology of the Indonesian nation, religion, culture, and virtue values formulated by the nation's ancestors and predecessors which have become good habits and are in line with the goals of national education.